Pengaruh Berbagai Luas Permukaan Daun Tanaman Lidah Mertua (Sansevieria trifasciata ‘Golden Hahnii’) Terhadap Penurunan Radiasi Komputer Ruang Kerja di RS KIA Sadewa, Yogyakarta - Dwi Larasati; Sri Muryani; Achmad Husein (Poltekkes Kemenkes Yogyakarta, 2016)
Computers, which are widely used by people to help finishing many tasks, have negative impact in the form of non-ionizing radiation. Based on the preliminary survey, the measurement of com-puter radiation in Sadewa Hospital had not exceeding the standard quality. However, continuous exposure will affect the health of the users. Sansevieria is one of plants which can reduce com-puter radiation. The purpose of this study was to know the influence of various leaves surface areas of Sansevieria trifasciata ‘Golden Hahnii’ in decreasing computer radiation. There were three treatment, i.e. A (510-570 cm2 leaves area), B (1020-1140 cm2 leaves area), and C (1530-1710 cm2 leaves area). The type of the research was a quasi experiment with pre-test post-test with control group design. The radiation mesurements were conducted toward 10 computers in 10 different rooms in the hospital. The results shows that radiation reduction yielded from treat-ment A was 0.142 x 10-4 mT, from treatment B was 0.277 x 10-4 mT, and from treatment C was 0.351 x 10-4 mT. The result of statistical test by using One Way Anova at 95 % level of signifi-cance obtained a p-value < 0,001, which means that the reduction difference among the results is significant. The subsequent LSD test concluded that treatment C yielded the highest reduction of computer radiation.